Review of 'Ageing, Ritual and Social Change: Comparing the Secular and Religious in Eastern and Western Europe' edited by Peter Coleman, Daniela Koleva, and Joanna Bornat - Edmondson, Ricca (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
---